A AND D SURFACTAN PROTEINS IN LUNG IMMUNE SYSTEM - Linawati, Ni Made (Medicina, 2012)
The surfactant associated proteins of  the lung are component of  lung innate immunity. Its functions in host defence is mediated by surfactant associated protein A and D. surfactant associated protein A and D are collectins familly, both synthesized and secreted by many cells in different parts of our body. (MEDICINA 2012;43:46-48).